Quantitative Comparison of Cephalogram and Cone-Beam Computed Tomography in the Evaluation of Alveolar Bone Thickness of Maxillary Incisors - Diyang Wei; Lingyun Zhang; Weiran Li; Yilin Jia (Galenos Yayinevi, 2020)
Objective:This study aims to quantitatively compare cephalogram and cone-beam computed tomography (CBCT) when evaluating maxillary central incisor alveolar bone thickness.Methods:We used 30 sets of lateral cephalograms and CBCT images that were recorded at the same time. Labial, buccal, and overall alveolar bone thicknesses were measured on three measurement lines of the forward-most incisor in lateral cephalograms and four maxillary incisors in CBCT images. Paired t-test, interclass correlation coefficient analysis, one-way analysis of variance (ANOVA), and Bland-Altman analysis were used to assess cephalometrically measured alveolar bone thickness of maxillary incisors and compare these measurements with those made using CBCT images.Results:Significant differences were observed between cephalometric and CBCT-based measurements of maxillary incisor alveolar bone thickness; most values showed mild or moderate correlation between the two methods. In most cases, cephalometric measurements were greater than CBCT-based measurements. Bland-Altman plots and ANOVA revealed that measurement bias increased when measurement lines moved apically. Alveolar bone thickness was always overestimated on cephalograms.Conclusion:Maxillary incisor alveolar bone thickness is always overestimated on cephalograms compared with CBCT-based measurements, with the overestimations ranging from 0.3 to 1.3 mm. Cephalometric measurement bias increases when measurement lines move apically. Thus, CBCT should be recommended when the accurate evaluation of alveolar bone thickness is warranted.